Pembangunan dan kebolehpercayaan item kesejahteraan sekolah rendah dalam kalangan murid, guru dan ibu bapa - Nor Shela Saleh; Khairunesa Isa; Muhaymin Hakim Abdullah; Sarala @ Thulasi Palpanadan; Hazila Kadir @ Sahar (Penerbit Universiti Kebangsaan Malaysia, 2022)
The school's well-being is critical in ensuring the people’s quality of life. Students, teachers, and parents are less motivated in successful teaching and learning sessions because of the bad environment. Using a pilot study method, this project will establish an aspect of primary school. Students, teachers, and parents were randomly assigned to receive questionnaires. There were 20 pupils, 18 teachers, and 20 parents as a result of the survey. Only 58 people responded to the survey. These findings are sufficient to determine the study's reliability. The findings of the pilot study revealed that the researcher was effective in developing the four parts of the primary school well-being index, including the status of the school environment, social interactions, students' self-achievement, and students' health levels. There are five different items in each element (questions). All items were allowed because they were reliable and had a Cronbach’s alpha value greater than 0.6. This signifies that no things are dropped because they are all of the medium, good, very excellent, or top quality. To summarise, the aspects in this investigation are trustworthy. As a result, the researcher will use this instrument to perform empirical research on the well-being index of school kids.